المعالجة المحاسبية لإهتلاك التثبيتات حسب النظام المحاسبي المالي Scf (مع دراسة حالات) - عوادي, مصطفى (جامعة الوادي - University of Eloued, 2012)
هدف هذا العمل هو تسليط بعض الضوء على هذا الموضوع لاستهلاك الأصول الثابتة في إطار نظام المحاسبة المالية الجديد خلافا للمخطط الوكني المحاسبي وقد أدخلت هذا النظام العديد من المفاهيم والمصطلحات والقواعد والقواعد الجديدة على البيئة المحاسبية الجزائرية وفقا لمعايير المحاسبة الدولية، وخاصة فيما يتعلق الأصول الثابتة وطرق الاستهلاك والقيود المحاسبية. هذا الموضوع ذو أهمية كبيرة للمؤسسة الاقتصادية لصيانته واستمراريته. لدراسة هذا الموضوع ، قسمناه إلى محورين: محور 1ST: رؤية النظام المحاسبي الجديد ومتطلبات التطبيق والفهارس في الجزائر والأهداف، فضلا عن الخلافات مع الإشارة المحاسبة الدولية. المحور الثاني: وجهة نظر أخرى حول الأصول الثابتة وفئاتها المختلفة ومفهوم الاستهلاك وطرق حسابها. بعد ذلك هناك فرق بين المخطط الوطني المحاسبي وscf حول موضوع تخصيص محاسبة الاستهلاك. The purpose of this work is to provide some clarification on the topic of asset depreciation under the new financial accounting system contrary to the NCP. This system introduced several concepts, terms, basics and new rules on the Algerian accounting environment according to international accounting standards, especially regarding fixed assets and depreciation methods and their accounting imputations. This subject is of great importance for the economic enterprise for its maintenance and continuity. To study this subject we divided it into two axes: 1st axis: A vision on the new accounting system and application requirements and concordances in Algeria, and their goals, as well as the differences with the international accounting reference. 2nd axis: Another view on fixed assets and their different categories and the concept of depreciation and their methods of calculation. After that, we can see the difference between the NCP and the SCF on the subject of depreciation.to conclude the accounting allocation of depreciation.
مقال
Keywords: النظام المحاسبي المالي، ومعايير المحاسبة الدولية، والأصول الثابتة والأصول الثابتة والأصول المتداولة، والاستهلاك، وهو ما يمثل تكلفة الاستهلاك والبيئة المحاسبية الجزائرية; Financial Accounting System, International Accounting Standards, Fixed Assets, Fixed Assets, Current Assets, Depreciation, Accounting Depreciation, Algerian Accounting Environment